2009
DOI: 10.1007/s11192-009-0143-6
|View full text |Cite
|
Sign up to set email alerts
|

Measuring technological diversification: identifying the effects of patent scale and patent scope

Abstract: Although technological diversification is an important strategic decision for both large and small firms alike, the conventional method of measuring such diversification may well introduce significant scale bias against small-and medium-sized firms. We examine this issue in this study using a sample of 73 Taiwanese integrated-circuit (IC) design firms covering the period from 1995 to 2007 and conclude that the conventional measure of technological diversification reflects the spread or distribution amongst tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 19 publications
0
27
0
1
Order By: Relevance
“…Previous studies have asserted that the number of IPCs that a company is involved with can be used as an indicator to assess the company's innovation performance (Hu and Rousseau, 2015). Studies have also claimed that an increase in IPCs that the patents of a company have corresponds to increases in both the diversification of technologies possessed by the company and the probability that the company enters a new technical area (Chen, Jang and Wen, 2010). The present study focussed on the number and values of IPCs for a single patent.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 98%
“…Previous studies have asserted that the number of IPCs that a company is involved with can be used as an indicator to assess the company's innovation performance (Hu and Rousseau, 2015). Studies have also claimed that an increase in IPCs that the patents of a company have corresponds to increases in both the diversification of technologies possessed by the company and the probability that the company enters a new technical area (Chen, Jang and Wen, 2010). The present study focussed on the number and values of IPCs for a single patent.…”
Section: Discussion and Managerial Implicationsmentioning
confidence: 98%
“…The most common of these is the lawsuit for patent infringement. At the beginning of production, if a manufacturer fails to carry out a detailed patent analysis of the relevant technology, it will face a painful price in the face of foreign manufacturers' recovery of royalties [27]. For the industry, the more detailed the patent information, the easier and more accurate it is for manufacturers to draw up the company's business strategy, R&D strategy, and patent strategy.…”
Section: Patent Analysismentioning
confidence: 99%
“…Next, based on the improved vocabulary query methods, a patent retrieval strategy was formulated by selecting keywords in every subfield. As shown in Figure 2, the determination of the ICM technology classification system and patent retrieval strategy refer to three kinds of documents: (1) research literature related to the ICM, whose research contents can be divided into patent bibliometrics [12,[39][40][41], developing situations [11][12][13]15], technology fields [14,18], etc. ; (2) industrial information related to the ICM, which includes industrial research reports [49,50], popular science books [51], etc.…”
Section: Technical Classification System and Data Collectionmentioning
confidence: 99%
“…For example, in an earlier study, patents issued to ICM enterprises from 1975 to 1994 were utilized to examine the effects of the value of a firm's technological advancement and of the newness of its technology on the probability of its failure [12]. In 2010, another study showed a bibliometric analysis of the patent publications of 73 Taiwanese IC design firms covering the period from 1995 to 2007 [39]. Using the patents from Taiwan and U.S. IC design and manufacturing firms, Tsai [40] shed light on the patent and Research and Development (R&D) spillover effects on productivity.…”
Section: Introductionmentioning
confidence: 99%